Evaluasi dan Penentuan Prioritas Resiko Keselamatan Kerja pada Area Departemen Machining Menggunakan Metode Failure Mode Effect Analysis (FMEA) di PT. Mitrametal Perkasa - Muhammad Fauzan; Ferida Yuamita (JOURNAL SAINS STUDENT RESEARCH, 2026)
PT Mitrametal Perkasa is a manufacturing company that faces various occupational hazards in its Machining Department, including machine entrapment, falling materials, cuts from sharp objects, and ergonomic-related risks. Based on recorded workplace accidents, risk identification and evaluation are necessary to improve occupational safety and health (OSH) performance within the company. This study aims to identify potential hazards, determine risk priorities, and propose risk control measures in the Machining Department of PT Mitrametal Perkasa. The Failure Mode and Effect Analysis (FMEA) method was employed, with data collected through observation, interviews, and literature review. Risk assessment was conducted using Severity (S), Occurrence (O), and Detection (D) parameters to calculate the Risk Priority Number (RPN). The results indicate that several hazards fall into the high-priority risk category and require immediate corrective actions. Proposed controls include improving compliance with personal protective equipment (PPE) usage, enhancing work procedures, conducting safety training, and strengthening workplace supervision. These measures are expected to reduce workplace accidents and improve OSH performance at PT Mitrametal Perkasa.